2020
DOI: 10.1111/pce.13785
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus addition increased carbon partitioning to autotrophic respiration but not to biomass production in an experiment with Zea mays

Abstract: Plant carbon (C) partitioning-the relative use of photosynthates for biomass production, respiration, and other plant functions-is a key but poorly understood ecosystem process. In an experiment with Zea mays, with or without arbuscular mycorrhizal fungi (AMF), we investigated the effect of phosphorus (P) fertilization and AMF on plant C partitioning. Based on earlier studies, we expected C partitioning to biomass production (i.e., biomass production efficiency; BPE) to increase with increasing P addition due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
(105 reference statements)
1
11
0
Order By: Relevance
“…These results are in line with the study by Řezáčová et al (2018), who reported photosynthetic upregulation following the establishment of mycorrhizal symbiosis. Also our follow-up experiment with a P gradient confirmed the important stimulating role of AMF for plant productivity and photosynthesis (see Ven et al, 2020b).…”
Section: Discussionsupporting
confidence: 71%
“…These results are in line with the study by Řezáčová et al (2018), who reported photosynthetic upregulation following the establishment of mycorrhizal symbiosis. Also our follow-up experiment with a P gradient confirmed the important stimulating role of AMF for plant productivity and photosynthesis (see Ven et al, 2020b).…”
Section: Discussionsupporting
confidence: 71%
“…The large plant residues incorporated into the topsoil provided substantial amounts of organic matter for microbial living and decomposition (Oelkers et al, 2015;Ven et al, 2020), which can stimulate microbial abundance and activities and promote microbial extracellular enzymes. These extracellular excretions play a fundamental role in microbial respiration and CO2 production, both of which stimulate silicate weathering and carbonate dissolution (Vicca et al, 2022).…”
Section: Determinants Of Sic Density In Different Soil Depthsmentioning
confidence: 99%
“…Given that mycorrhizal fungi depend on their host for C, their influence on ESW is likely to be strongly related to plant activity and plant C allocation. Depending on soil conditions, plants can allocate substantial amounts of C to mycorrhizal fungi (Ven et al, 2020), and thereby stimulate their weathering activity, increasing the release of P and other mineral elements from the silicate minerals (Verbruggen et al, 2021).…”
Section: Biota Stimulating Silicate Weatheringmentioning
confidence: 99%
“…Plants allocate substantial amounts of C belowground in the form of roots and exudates and through symbiosis with mycorrhizal fungi (Ven et al, 2019; Verlinden et al, 2018). Nutrient availability is a key driver of plant C allocation and plant C inputs to the soil are likely to be affected by silicate addition, although the magnitude and direction of the effect is expected to depend on environmental conditions (Litton et al, 2007; Poorter et al, 2012; Ven et al, 2020; Vicca et al, 2012). Especially soil nutrient status and plant growth responses to the silicate additions are expected to be important in this regard.…”
Section: Impact Of Esw On Soc Storagementioning
confidence: 99%